2004
DOI: 10.1897/03-50
|View full text |Cite
|
Sign up to set email alerts
|

Utility of morphological abnormalities during early‐life development of the estuarine mummichog, Fundulus heteroclitus, as an indicator of estrogenic and antiestrogenic endocrine disruption

Abstract: To evaluate the use of morphological abnormalities for standard testing of endocrine-disrupting substances (EDS), we tested the hypothesis that developmental abnormalities are a sensitive indicator of exposure to waterborne estrogenic and antiestrogenic EDS during embryonic, larval, and juvenile stages in the common estuarine killifish, the mummichog (Pisces: Cyprinodontidae). Static exposures with daily renewal were carried out with 10 to 10,000 ng/L of the estrogen agonist 17alpha-ethynylestradiol (EE2) or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 44 publications
(109 reference statements)
3
30
0
1
Order By: Relevance
“…F. heteroclitus has been used as a model species for several recent studies of endocrine disruption. In particular, laboratory and natural populations exposed to environmental contaminants show altered levels of sex steroids (Dube & MacLatchy 2001, Hewitt et al 2002, MacLatchy et al 2003, Boudreau et al 2004, Greytak et al 2005, thyroid hormones (Zhou et al 2000, Carletta et al 2002, and aromatase mRNA (Greytak et al 2005). Given the cross-talk between mammalian ERs and ERRs (Vanacker et al 1999a, Giguere 2002, and the hypothesized regulatory role of ERRa in aromatase and thyroid receptor expression (Vanacker et al 1998, Yang et al 1998, elucidation of ERR signaling may provide insight into endocrine regulation and disruption in this model species.…”
Section: Introductionmentioning
confidence: 99%
“…F. heteroclitus has been used as a model species for several recent studies of endocrine disruption. In particular, laboratory and natural populations exposed to environmental contaminants show altered levels of sex steroids (Dube & MacLatchy 2001, Hewitt et al 2002, MacLatchy et al 2003, Boudreau et al 2004, Greytak et al 2005, thyroid hormones (Zhou et al 2000, Carletta et al 2002, and aromatase mRNA (Greytak et al 2005). Given the cross-talk between mammalian ERs and ERRs (Vanacker et al 1999a, Giguere 2002, and the hypothesized regulatory role of ERRa in aromatase and thyroid receptor expression (Vanacker et al 1998, Yang et al 1998, elucidation of ERR signaling may provide insight into endocrine regulation and disruption in this model species.…”
Section: Introductionmentioning
confidence: 99%
“…The chorion (egg envelope) often has a barrier role in protecting fish embryos against exogenous substances or toxic ions (Boudreau et al, 2004). We demonstrated that embryonic exposure to environmentally relevant to micromolar levels of KET and MET delayed the heart rate and hatching time ( Figure 1) and increased the incidence of developmental abnormality (e.g., hemorrhage and defects in the eye and/or heart) ( Table S3, SI).…”
Section: Discussionmentioning
confidence: 79%
“…In both laboratory and field studies, killifish have been used to document effects of environmental chemicals on many different end-points of reproduction and development such as viability and fertilizability of eggs and sperm (Khan and Weis, 1987a), cytogenetic effects (Crawford and Guarino, 1976;Perry et al, 1988;Black et al, 1998a,b), embryo mortality, rate of development, developmental deformities, time to hatching and hatching success (Weis and Weis, 1974;Crawford and Guarino, 1976;Weis and Weis, 1977;Black et al, 1998a,b;Ownby et al, 2002;Boudreau et al, 2004;Wassenberg and Di Giulio, 2004b;Boudreau et al, 2005;Wassenberg et al, 2005;Gonzalez et al, 2006;Timme-Laragy et al, 2006), as well as larval growth, spontaneous activity, prey-capture ability, startle response, learning ability, neurotransmitter levels (Zhou et al, 1999;Zhou et al, 2001;Weis et al, 2003;Timme-Laragy et al, 2006) and sex ratios (Matta et al, 2001). End-points used to assess reproductive condition of sexually mature adults include reproductive success, circulating sex steroids, gonadal size, hepatic size, yolk protein synthesis, and genetic markers such as CYP19 aromatases, ER and vitellogenin (Black et al, 1998a,b;Monteverdi and Di Giulio, 2000;Matta et al, 2001;MacLatchy et al, 2003;Boudreau et al, 2004;Boudreau et al, 2005;Greytak et al, 2005;Greytak and Callard, 2007).…”
Section: Reproductive and Developmental Effectsmentioning
confidence: 99%
“…End-points used to assess reproductive condition of sexually mature adults include reproductive success, circulating sex steroids, gonadal size, hepatic size, yolk protein synthesis, and genetic markers such as CYP19 aromatases, ER and vitellogenin (Black et al, 1998a,b;Monteverdi and Di Giulio, 2000;Matta et al, 2001;MacLatchy et al, 2003;Boudreau et al, 2004;Boudreau et al, 2005;Greytak et al, 2005;Greytak and Callard, 2007).…”
Section: Reproductive and Developmental Effectsmentioning
confidence: 99%